2013
DOI: 10.1073/pnas.1320565110
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer originating in basal cells progresses to adenocarcinoma propagated by luminal-like cells

Abstract: The relationship between the cells that initiate cancer and the cancer stem-like cells that propagate tumors has been poorly defined. In a human prostate tissue transformation model, basal cells expressing the oncogenes Myc and myristoylated AKT can initiate heterogeneous tumors. Tumors contain features of acinartype adenocarcinoma with elevated eIF4E-driven protein translation and squamous cell carcinoma marked by activated betacatenin. Lentiviral integration site analysis revealed that alternative histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
158
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 145 publications
(174 citation statements)
references
References 53 publications
13
158
1
2
Order By: Relevance
“…S2). As a positive control, we used a human CRPC model initiated in primary human cells and driven by the combination of Myc and myristoylated/activated AKT (myrAKT) oncogenes that express high levels of NICD1 (36). NICD1 (100 kDa) was observed only in the human metastatic CRPC samples and the Myc/myrAKT human CRPC model (36) but not in the benign tissue or in localized low-to intermediate-risk prostate cancers ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2). As a positive control, we used a human CRPC model initiated in primary human cells and driven by the combination of Myc and myristoylated/activated AKT (myrAKT) oncogenes that express high levels of NICD1 (36). NICD1 (100 kDa) was observed only in the human metastatic CRPC samples and the Myc/myrAKT human CRPC model (36) but not in the benign tissue or in localized low-to intermediate-risk prostate cancers ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The differentiation of basal cells with preexisting prooncogenic signaling into luminal cells would enhance the susceptibility of luminal cells to transformation by ensuing genetic changes, as demonstrated by our current study and by several previous studies using mouse models (14-16, 19, 61). A very recent study using the prostate regeneration model showed that basal cells even may serve as the origin of prostate cancer stem cells (62). Currently, because of technical limitations, no published study has directly demonstrated that basal cells and luminal cells within the same human PIN lesions share genetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Murine models overexpressing key components of developmental signaling pathways alone or with other genetic alterations can drive a phenotype reminiscent of late-stage prostate cancer (19)(20)(21)(22). Although these studies provide evidence of a relationship between stem-like qualities and an aggressive phenotype, no studies to our knowledge have shown a molecular relationship between aggressive prostate cancer and uncultured stem-like cells from the human prostate.…”
Section: Significancementioning
confidence: 99%